2015
DOI: 10.1515/mper-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Analysis of Tissue Paper Manufacturing From Virgin Pulp or Recycled Waste Paper

Abstract: The aim of this work is to compare the environmental impacts of two production processes of tissue paper using virgin pulp (virgin fiber) or waste paper pulp (recycled fiber). This comparison is based on the materials and energy used as well as emissions and waste resulting from the production of tissue paper. Life cycle assessment (LCA), ReCiPe method, was chosen as the analysis tool. The results of the research proved that electricity has the most considerable participation in the overall environmental impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…They ranged from 1 78 to 17. 72 As more impact categories are included, the picture of the potential environmental impact becomes clearer. Furthermore, the studies also covered different geographies, wood species and pulping methods.…”
Section: Available Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…They ranged from 1 78 to 17. 72 As more impact categories are included, the picture of the potential environmental impact becomes clearer. Furthermore, the studies also covered different geographies, wood species and pulping methods.…”
Section: Available Literaturementioning
confidence: 99%
“…Only one of the LCAs compared the use of virgin and recycled fibres. 72 This study only investigates the pulp and paper production stages, reasoning that other studies have shown that the forestry and end of life stages do not have relevant contributions. The results show that the production of 1 ton of tissue paper from recycled paper has a lower environmental impact than when using virgin fibres.…”
Section: Environmental Impact Of the Life-cycle Stagesmentioning
confidence: 99%
See 3 more Smart Citations